Pengaruh Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi di Provinsi Sulawesi Tengah - Nuriva Mawaddah Andani; Muhtar Lutfi; Edhi Taqwa; Rita Yunus; Musdayati (AKUNTANSI 45, 2026)
This study aims to analyze and quantify the influence of government spending on economic growth in Central Sulawesi Province. Amid the regional economic dynamics following the COVID-19 pandemic and the implementation of regional autonomy, government expenditure, as reflected in the Regional Budget (APBD), plays a crucial role as a fiscal policy instrument to stimulate development. This research employs a quantitative approach with an associative design, utilizing annual time-series secondary data from 2020 to 2023 sourced from the Central Statistics Agency (BPS). Data analysis was conducted using a simple linear regression method with EViews 12 software to test the research hypothesis. The findings indicate that government spending has a significant and positive effect on economic growth. This is evidenced by a regression coefficient of 1.153 and a significance level of 0.0246 (p < 0.05). The model demonstrates a very high explanatory power, with an R-Squared value of 0.9993, indicating that 99.93% of the variation in economic growth can be explained by government spending. This study confirms that effective budget allocation to productive sectors, such as infrastructure and human capital, is a strategic driver of regional economic growth, making efficient management of the APBD key to successful regional development.